Functional Quality and Microbiological Stability of Grape Juice During Processing by UV-C Light Compared to Mild Heat Treatment and Evolution of the Parameters During Cold Storage - Cielo Char; Carla Vegas; Nalda Romero; Luis Puente-Diaz; Jaime Ortiz-Viedma; Marcos Flores (Foods, 2025)
The effect of UV-C was assessed on microbiological stability, functional compounds, and quality factors of white grape juice compared to mild thermal treatment (MTT). The inactivation kinetics of Escherichia coli (target microorganism) and Saccharomyces cerevisiae in grape juice by UV-C and MTT (75 °C) were evaluated to define the processing time. The comparative effect on the functional compounds was evaluated. Additionally, microbiological stability and quality factors were assessed during storage at 4 °C. The grape juice was characterized (pH 3.7, 25 °Brix, absorption coefficient 44.2 cm−1, total phenols (TP) 214 mg GAE/L). UV-C (569 mJ/cm2) reduced E. coli to 5.03 log CFU/mL in 12.5 min, preserved TP (235 mg GAE/L), and antioxidant capacity (AC 4.5 mM TE/L). Thermal treatment reduced E. coli to 5.14 log CFU/mL in 180 s, increased TP (237–312 mg GAE/L), and maintained the AC of the juice. During storage, UV-C and MTT controlled microbiota growth, extending the time of microbiological stability by 42%. All the treatments showed a similar gradual loss of TP during storage. However, MTT has better-preserved color parameters. In conclusion, UV-C was effective from a microbiological perspective without compromising the functional quality of juice. However, further research is needed to improve color.